Analisis Tindak Tutur Lokusi dalam Daftar Putar “Zental Health” pada Saluran Youtube Zenius - Novi Amelia Oktaviani; Avita Setiawati; Hidayatul Afifah; Trista Etika Putri; Dita Luluk Safitri; Asep Purwo Yudi Utomo; Limpad Nurrachmad (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Locutionary speech acts are a type of speech act that focuses on the meaning of a sentence. This research is based on speakers whose pronunciation does not emphasize actual speech. The aim of this research is to describe the form and intent of locutionary speech acts in the "Zental Health"playlist on the Zenius YouTube channel. The research approach used is pragmatic, with qualitative methods in the form of descriptive research. This research uses a data collection method using free listening and note-taking techniques. At the data analysis stage, we used the divide and match method. Meanwhile, the analysis presentation technique used is informal. This research produced several locutionary speech acts contained in 4 videos on the "Zental Health" playlist on the Zenius YouTube channel, which contains 40 data points, including 16 news speech acts, 19 question speech acts, and 5 command speech acts. With this research, the author hopes that it can provide benefits for readers and other researchers as a reference source regarding locutionary speech acts.